Effect of intermetallic compounds distribution on bonding strength of steel–aluminum laminates. (October 2022) - Deng, Zejun; Xiao, Hong; Yu, Chao
Graphical abstract: Highlights: Granular IMCs with spaced distribution can limits the expansion of cracks and changes the direction of the cracks. Granular IMCs with spaced distribution can change the position of maximum shear stress from bonding interface to aluminum matrix. The Kirkendall voids form a crack source and expand rapidly, when the lamellar IMCs is formed. Abstract: In this study, steel–Al laminates are prepared via hot-roll bonding and annealed for various durations to generate intermetallic compounds (IMCs) with different distributions at the interface. The fracture forms of the laminates with different IMCs distributions are analyzed via in-situ tensile–shear experiments, and the shear stress distribution in the regions adjacent to the bonding interface during the tensile–shear process is investigated via finite element modeling using Abaqus. Results show that granular IMCs can change the direction of cracks and limit crack expansion during the tensile–shear process. The location of the maximum shear stress shifts from the interface to the aluminum matrix, causing fracture to be generated in the Al matrix. When an approximate IMC layer is formed at the bonding interface, the maximum shear stress occurs at the IMC–Al interface. Additionally, Kirkendall voids, which are the source of cracks, are observed at the IMCs–Al interface. They expand along the IMC–Al interface during the tensile–shear process, thus reducing the bonding strength. This study shows that granular IMCs are beneficial for improving the bonding strength, and that the bonding strength begins to deteriorate when the IMCs accumulate to form a layer.